4D flow MRI can detect subtle right ventricular dysfunction in primary left ventricular disease. Issue 3 (24th July 2015) - Fredriksson, Alexandru Grigorescu; Svalbring, Emil; Eriksson, Jonatan; Dyverfeldt, Petter; Alehagen, Urban; Engvall, Jan; Ebbers, Tino; Carlhäll, Carl‐Johan
Abstract : Purpose: To investigate whether 4D flow magnetic resonance imaging (MRI) can detect subtle right ventricular (RV) dysfunction in primary left ventricular (LV) disease. Materials and Methods: 4D flow and morphological 3T MRI data were acquired in 22 patients with mild ischemic heart disease who were stratified into two groups based on LV end‐diastolic volume index (EDVI): lower‐LVEDVI and higher‐LVEDVI, as well as in 11 healthy controls. The RV volume was segmented at end‐diastole (ED) and end‐systole (ES). Pathlines were emitted from the ED volume and traced forwards and backwards in time to ES. The blood volume was separated into flow components. The Direct Flow (DF) component was defined as RV inflow passing directly to outflow. The kinetic energy (KE) of the DF component was calculated. Echocardiographic conventional RV indices were also assessed. Results: The higher‐LVEDVI group had larger LVEDVI and lower LV ejection fraction (98 ± 32 ml/m 2 ; 48 ± 13%) compared to the healthy (67 ± 12, P = 0.002; 64 ± 7, P < 0.001) and lower‐LVEDI groups (62 ± 10; 68 ± 7, both P < 0.001). The RV 4D flow‐specific measures "DF/EDV volume‐ratio" and "DF/EDV KE‐ratio at ED" were lower in the higher‐LVEDVI group (38 ± 5%; 52 ± 6%) compared to the healthy (44 ± 6; 65 ± 7, P = 0.018 and P < 0.001) and lower‐LVEDVI groups (44 ± 6; 64 ± 7, P = 0.011 and P < 0.001). There was no difference in any of the conventional MRI and echocardiographic RV indices between the three groups. Conclusion: We found that in primary LV disease mild impairment of RV function can be detected by 4D flow‐specific measures, but not by the conventional MRI and echocardiographic indices. J. MAGN. RESON. IMAGING 2016;43:558–565.